Exploring indicator scoring as a selection tool in plant breeding: A study under conservation vs conventional tillage systems - Sagar, Vidya; Yadav, Rajbir; Gaikwad, Kiran B.; Gupta, Soma (The Indian Journal of Genetics and Plant Breeding, 2016)
Indian agriculture is on an edge of transition from conventional to conservation agriculture, the only limiting constrant is avaliblity of cultivars adapted to conservation agriculture. This study explores possibility of indicator scoring system for identification of genotypes suitable forÂ different tillage management system namely, conventional tillage flat bed (CTFB) and conservation agriculture (CA). Minimum data set (MDS) was constructed by selecting the traits from each of five principal components (PC) accounting for 71.26% of total variation. Multiple linear regression between MDS as independent variable and yield and biomass as dependent variable showed R2 value of 0.661 and 0.605. Indicator score identified through nonlinear scoring of the MDS found out CA as a superior environemt to conventional agriculture in both years. Indicator score identified HD3117 and HDCSW 18 for CA which support the use of indicator scoring as a selection tool in plant breeding as both of these lines are the product of systematic breeding under CA condition and have revealed significant superiority over other in multilocational yield trials for CA.